Naringin promotes osteoblast differentiation and ameliorates osteoporosis in ovariectomized mice - Yubo Cui; Zhijun Yang; Guisong Yu; Jihui Hu; Dian Li; Xing Fu; Wenlong Yang; Fengyun Yang (Scientific Reports)
Abstract This study aimed to investigate the anti-osteoporotic mechanisms of naringin in osteoblasts and mice. In vitro, MC3T3-E1 cells were treated with naringin to detect cell proliferation, alkaline phosphatase (ALP) activity, and calcified nodule formation. Western blot was used to analyze the expression of osteogenic markers (OPN, COL1A1, RUNX2) and Wnt/β-catenin pathway proteins (Wnt3a, β-catenin). In vivo, ovariectomized (OVX) mice were treated with naringin for 3 months to observe bone microstructure, femoral histomorphology, and marker expression. Results showed that 0.1, 0.5, and 1 µmol/L naringin significantly promoted cell proliferation, enhanced ALP activity, and increased calcified nodule formation. Naringin also improved bone mineral density (BMD) and trabecular bone number in OVX mice. It elevated serum levels of bone formation markers (P1NP, OCN) while reducing the bone resorption marker CTX-1. Both in vitro and in vivo, naringin upregulated OPN, COL1A1, RUNX2, Wnt3a, and β-catenin expression, and induced β-catenin nuclear translocation. Notably, naringin antagonized the inhibitory effects of XAV939 (a Wnt/β-catenin pathway inhibitor) on OPN, COL1A1, and RUNX2 protein expression. These findings demonstrate that naringin enhances bone density in OVX mice and promotes osteogenic differentiation of MC3T3-E1 cells via activation of the Wnt/β-catenin pathway.